Evidence Based Practice Relaksasi Nafas Dalam dengan Penurunan Nyeri Gouth Artritis - Nindi, Engryne; Angwarmase, Yohana (Yayasan Syalom Cipta Sumikolah, 2025)
The elderly are one of the groups at risk (population at risk). This is because the elderly have health problems which may develop into worse ones due to influencing factors. Problems that often arise include functional and organ disorders, as well as geriatric syndromes such as incontinence, sleep disorders, malnutrition, pain and falls. One of the most common syndromes found in the elderly is joint pain, gout arthritis, this disease, if without effective treatment, can cause severe kidney function disorders and a decrease in quality of life. In general, gout arthritis is caused by foods high in purine, the symptoms caused by gout arthritis. in the form of pain in the joints and stiffness in the joints, so there is a need for therapeutic management, both pharmacological and non-pharmacological, to reduce joint pain, which can be done by providing deep breathing relaxation therapy. The aim of this scientific work is to implement Deep Breathing Relaxation Therapy to Reduce Gouth Arthritis Pain in Mrs. A At the Peaceful Nursing Home Ranomuut Manado. The results of research using evidence based nursing providing deep breathing relaxation therapy with reducing gout arthritis pain in Mrs. A, which was carried out for 3 days, the evaluation results showed that deep breathing relaxation therapy was effective in reducing gout arthritis pain in Mrs. A. Conclusion: this scientific work shows a reduction in gout arthritis pain in Mrs. A after being given deep breathing relaxation therapy. Suggestion: hopefully the results of this research can increase knowledge and be able to provide nursing care to clients with gout arthritis pain problems and be able to implement nursing interventions based on the Evidence Based Practice approach.